A modified precise integration method based on Magnus expansion for transient response analysis of time varying dynamical structure. (August 2016) - Yue, Cong; Ren, Xingmin; Yang, Yongfeng; Deng, Wangqun
Abstract: This paper provides a precise and efficacious methodology for manifesting forced vibration response with respect to the time-variant linear rotational structure subjected to unbalanced excitation. A modified algorithm based on time step precise integration method and Magnus expansion is developed for instantaneous dynamic problems. The iterative solution is achieved by the ideology of transition and dimensional increment matrix. Numerical examples on a typical accelerating rotation system considering gyroscopic moment and mass unbalance force comparatively demonstrate the validity, effectiveness and accuracy with Newmark- β method. It is shown that the proposed algorithm has high accuracy without loss efficiency.